2019
DOI: 10.1021/acscatal.9b03790
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Instability of Metal–Organic Frameworks: In Situ Spectroelectrochemical Investigation of the Real Active Sites

Abstract: Despite recent attempts using metal–organic frameworks (MOFs) directly as electrocatalysts, the electrochemical stability of MOFs and the role of in situ-formed species during electrochemistry are elusive. Using in situ spectroelectrochemistry, we present herein a comprehensive discussion on the structural and morphological evolution of MOFs (zeolitic imidazolate framework-67, ZIF-67) during both cyclic voltammetry and amperometry. Dramatic morphological changes exposing electron-accessible Co sites are eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
252
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(262 citation statements)
references
References 49 publications
(90 reference statements)
8
252
2
Order By: Relevance
“…This trend is also observed in Zn 100− x Co x ‐ZIF‐8 samples (Figure S16 in the Supporting Information) and can be attributed to increased electrolyte accessibility to the hydrophobic ZIF‐67 structure over time. FTIR, SEM, XPS, and PXRD characterizations of the Zn 100− x Co x ZIF‐8 samples after the OER durability tests reveal transformation of the ZIFs to an active cobalt‐based oxide/oxyhydroxide nanophase, in a good agreement with the literature reports (Figures S17–S20 in the Supporting Information) [9–11, 17, 42–44] . As shown in Figure S17 (in the Supporting Information), the FTIR spectra show the development of a new Co−O vibrational mode (at 523 cm −1 ) at the expense of Zn/Co‐N coordination (at 420 cm −1 ) in the Zn 100− x Co x ZIF‐8 samples.…”
Section: Resultssupporting
confidence: 88%
“…This trend is also observed in Zn 100− x Co x ‐ZIF‐8 samples (Figure S16 in the Supporting Information) and can be attributed to increased electrolyte accessibility to the hydrophobic ZIF‐67 structure over time. FTIR, SEM, XPS, and PXRD characterizations of the Zn 100− x Co x ZIF‐8 samples after the OER durability tests reveal transformation of the ZIFs to an active cobalt‐based oxide/oxyhydroxide nanophase, in a good agreement with the literature reports (Figures S17–S20 in the Supporting Information) [9–11, 17, 42–44] . As shown in Figure S17 (in the Supporting Information), the FTIR spectra show the development of a new Co−O vibrational mode (at 523 cm −1 ) at the expense of Zn/Co‐N coordination (at 420 cm −1 ) in the Zn 100− x Co x ZIF‐8 samples.…”
Section: Resultssupporting
confidence: 88%
“…Fortunately,r oughening the surface of composite nanomaterials is more conducive to absorbing N 2 ,a nd the combination of ZIF-67 with POMs into polyhedron preventP OMs aggregation,w hich overcomes the shortcomings of the smalls urface area of POMs, thereby increasing more active sites and improving catalytic N 2 performance. [45,46] At the same time, energy dispersive X-ray (EDX) elementm apping reveals that the composite nanomaterials contain all the elementso fZ IF-67 and POMs, demonstrating the successful recombination of ZIF-67 and POMs, and the same evidence is tested by energy-dispersive spectrometry (EDS, Figures S5-S16).…”
Section: Resultsmentioning
confidence: 72%
“…Indeed, the degradation of ZIF‐8 in water due to hydrolysis has been reported and well investigated recently . Recent studies also show that ZIF‐67 shows limited stability in water , and the use of ZIF‐67‐based modified electrodes in alkaline electrolytes can electrochemically convert ZIF‐67 into MOF‐derived cobalt hydroxide ; it is thus reasoned that ZIF‐67 would be another option of precursors to prepare the electrochemically active MOF‐derived cobalt hydroxide for electroanalysis. Several studies have demonstrated the applications of ZIF‐8 and related ZIF‐based materials for sensing the environmental contaminants in aqueous solutions .…”
Section: Chemically Stable Mofsmentioning
confidence: 99%